Genetic diversity in muskmelon (Cucumis melo) - MADHUMATHI, C; REDDY, D SRINIVASA; PRASAD, B HARI VARA (The Indian Journal of Agricultural Sciences, 2020)
The present investigation was carried out during 2014-15 and 2015–16 at Horticultural Research Station, Ananthrajupet, DRYSRHU, Andhra Pradesh to assess the genetic diversity in muskmelon, Cucumis melo. Genetic divergence evaluated using Mahalanobis D2 analysis revealed less to moderate diversity among fourty two genotypes. The cluster analysis of muskmelon exhibited a moderate clustering pattern and grouped genotypes into five distinct clusters with maximum of 37 genotypes in cluster I, two in cluster IV and one in each of cluster II, III and V. The highest inter-cluster distance (80.61) between Cluster III and IV indicating the genotypes of these clusters may give heterotic response and leads to better segregants. Among the morphological traits studied, fruit length (23.69%), pulp thickness (17.07%) and fruit girth (16.84%) contributed major share in the divergence of the genotypes which can be utilized for selection of individual genotypes for future crop improvement programme. Most of the genotypes accommodated into single cluster, probably they may share genetic similarity. The genotypes Papayee S-1, IC 321371, Kundan, Muskan and Arka Jeet, being divergent from others may serve as potential parents for breeding programmes.